Ein Textvorschlag zu Ov. met. 1.591 - Thomas Gärtner (Exemplaria Classica, 2010)
In Ov. met. 1.591, where the majority of manuscripts has Altorum nemorum, the deixis necessitated by the context is provided by the emendation En horum nemorum.